1987
DOI: 10.1002/bms.1200140815
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate esters and semen quality parameters

Abstract: Analysis of reports in the world's literature suggests that average sperm densities for groups of unselected males were relatively constant at about 108 million cells per ml prior to 1950. Subsequent to that time mean sperm densities appear to have declined. Regression analysis indicates the existence of significant negative correlations between mean sperm densities and production of synthetic organic chemicals among other parameters. Phthalate esters are one class of large volume organic chemicals that are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 45 publications
0
29
0
2
Order By: Relevance
“…In conjunction with this are reports that indicate a significant decrease in the quality of human semen [2][3][4] . It is estimated that male-related disorders are probably present in up to 40% to 50% of childless couples, alone or in combination with female factors [5,6] .…”
Section: Introductionmentioning
confidence: 74%
“…In conjunction with this are reports that indicate a significant decrease in the quality of human semen [2][3][4] . It is estimated that male-related disorders are probably present in up to 40% to 50% of childless couples, alone or in combination with female factors [5,6] .…”
Section: Introductionmentioning
confidence: 74%
“…A substantial proportion of the limited human studies on phthalates and reproductive effects in adults have been focused on investigating associations with altered semen quality. In an early study, Murature et al (1987) measured DBP concentrations in the cellular fractions of ejaculates from 21 university students and found an inverse relationship with sperm concentration. The study had a number of limitations, including a small number of participants, the failure to adjust for potential confounders and measurement of the parent compound, which may be subject to sample contamination.…”
Section: Phthalates (A) Exposurementioning
confidence: 99%
“…Recent reports have suggested that semen quality has declined during the past 50 years (8)(9)(10)(11)(12)(13)(14)(15). However, these studies examined predominantly groups of selected individuals such as semen donors (10), candidates for vasectomy (8), or patients from infertility clinics (11)(12)(13)15).…”
Section: Semen Qualitymentioning
confidence: 99%